EUCALYPTUS FOREST RESIDUES POTENTIAL TO MITIGATE GHG EMISSIONS IN BRAZIL: A CASE STUDY FOR SÃO PAULO AND ITS INTERFACE WITH LOW-CARBON POLICIES - Nogueira, G. P. [UNESP]; Petrielli, G. P.; Hernandes, T. A.D.; Romero, C. W.S.; Lamparelli, R. A.C.; Franco, T. T.; Dias, M. O.S.; Cavaliero, C. K.N. [UNESP] (My University, 2022)
Brazil’s emerging low-carbon policy, RenovaBio, has given biofuels producers a new chance to translate life-cycle carbon footprint into actual revenue. This allows alternative and residual biomasses to be explored for cellulosic ethanol production, since little to no burden is attributed to these feedstocks from their cultivation phases, such as the case for eucalyptus forest residues (EFR). This work, thus, proposes a biorefinery configuration for ethanol and electricity coproduction from EFR, and correlates this process route with residue availability and with RenovaBio’s decarbonization credits (CBIO), by prospecting specific regions within São Paulo state, the second biggest eucalyptus producer in the country. The baseline EFR availability (1.65 t.ha-1.year-1) returned a sizable ethanol production scale (152.3 ML.year-1) with a 120 km coverage radius, that would mitigate 189 ktCO2eq.year-1 in substitution to gasoline, corresponding to 0.5% of RenovaBio’s target for 2022 and an equivalent 3.7 mi US$ in CBIOs. This approach, however, disclosed how discrepant EFR availability data is over the literature, which severely compromises these conclusions. Such issues could be overcome by adopting a regionalized and georeferenced strategy in future works.
Keywords: biorefinery; ethanol; eucalyptus; forest residues; geographical information system (GIS); greenhouse gases (GHG)